AN ANALYSIS OF STUDENTS’ ERRORS IN PRONOUNCING ENGLISH DIPHTHONGS AT THE FIRST SEMESTER OF STAIN JURAI SIWO METRO - Much Deiniatur (Jurnal Pedagogy, 2016)
The objectives of this research are to find out total errors of the student when they pronouncing English word containing diphthongs, to find out what type of diphthongs that students made the most frequently mispronounced, to find out what type of diphthongs that students made the least frequently mispronounced, and to find out the factors influencing error pronunciation that the student made in English word containing diphthongs.In this research the writer used qualitative method. The subjects of this research were 40 of the First Semester students at STAIN Jurai Siwo Metro in academic year 2015/2016. The instrument of this research was a pronunciation test of the English word containing 9 types of English diphthongs, and voice recorder to record the students’ pronounciation.The data of this research were collected by giving the English pronunciation test. The collected data were identified, classified, analyzed and interpreted.. The results of the analysis showed that the students made errors out of the total 499 words. The types of diphthongs that the students the most frequently mispronounced are [oʊ] (62 words), [aʊ] (61 words), [ʊə] (59 words), [ɔə] (59 words), and [ɛə] ( 58 words),.The type of diphthongs that the students the least frequently mispronounced is [aɪ] (46 word).The factors influencing error pronunciation that the students made are the habit of students in pronouncing the word that contains of diphthongs and the students pronounced the word as it was written in the orthographic writing.